2021
DOI: 10.1101/2021.02.15.431262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial tryptophan catabolism affects the vector competence ofAnopheles

Abstract: The influence of microbiota on mosquito physiology and vector competence is becoming increasingly clear but our understanding of interactions between microbiota and mosquitoes still remains incomplete. Here we show that gut microbiota of Anopheles stephensi, a competent malaria vector, participates mosquito tryptophan metabolism. Elimination of microbiota by antibiotics treatment leads to the accumulation of tryptophan (Trp) and its metabolites, kynurenine (Kyn), 3-hydroxykynurenine (3-HK) and xanthurenic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…A study by Feng et al, demonstrated the influence of gut microbiota of Anopheles stephensi (a potent malaria vector) on tryptophan metabolism. The study reported how elimination of gut microbiota via antibiotics increased accumulation of tryptophan and its metabolites (kynurenine and 3-hydroxykynurenine, 3H-K) in the mosquito with high levels of 3H-K leading to structural impairments in the peritrophic matrix which in turn facilitated Plasmodium berghei infection (Feng et al, 2021). Similar observations were also made by Das de et al (Das De et al, 2022),.…”
Section: The Gut Microbiome Influences Metabolic Homeostasis In the M...supporting
confidence: 54%
See 1 more Smart Citation
“…A study by Feng et al, demonstrated the influence of gut microbiota of Anopheles stephensi (a potent malaria vector) on tryptophan metabolism. The study reported how elimination of gut microbiota via antibiotics increased accumulation of tryptophan and its metabolites (kynurenine and 3-hydroxykynurenine, 3H-K) in the mosquito with high levels of 3H-K leading to structural impairments in the peritrophic matrix which in turn facilitated Plasmodium berghei infection (Feng et al, 2021). Similar observations were also made by Das de et al (Das De et al, 2022),.…”
Section: The Gut Microbiome Influences Metabolic Homeostasis In the M...supporting
confidence: 54%
“…This is important to prevent Plasmodium spp. Infections (Okech et al, 2006;Lima et al, 2012;Feng et al, 2021;Bottino-Rojas et al, 2022). Microbiota also plays a role in enhancing/blocking viral infections by secreting metabolites or altering metabolic homeostasis (Apte-Deshpande et al, 2012;Ramirez et al, 2012;Apte-Deshpande et al, 2014;Ramirez et al, 2014).…”
Section: Adult Mosquitoesmentioning
confidence: 99%
“…This metabolite induces Plasmodium berghei infection in Anopheles mosquitoes by damaging the structure of the peritrophic matrix in the midgut. Nevertheless, it has been shown that the gut microbiota (i.e., Pseudomonas alcaligenes ) in A. stephensi helps in improving the resistance towards malaria parasites by synthesizing the enzyme kynureninase that catabolizes 3-HK [ 5 , 6 ]. Although the potential toxicity of 3-HK has been highlighted in many studies, it remains present in various physiological functions as a compound of significance.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that tryptophan catabolism has a role in modulating insecticide tolerance in permethrin-treated Drosophila melanogaster [ 135 ]. Likewise, this pathway was described in Anopheles , where catabolism of 3-hydroxykynurenine (3-HK), a metabolite of tryptophan by Pseudomonas , had a role in vectorial competence, protecting mosquitoes against Plasmodium infection [ 136 ]. ATP-binding cassette (ABC) transporters regulated by a two-component system (TCSs) were another predicted function in Pseudomonas .…”
Section: Discussionmentioning
confidence: 99%